Craniofacial Trauma Diagnosis and Management - Hardt, Nicolas; Kuttenberger, Johannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Craniofacial Trauma, Diagnosis and Management offers detailed guidance on the diagnosis, surgical planning, and interdisciplinary treatment of craniofacial trauma. The book is divided into two parts. The first, devoted to classification and diagnosis of craniofacial fractures, includes chapters on anatomy, radiology, fracture classification, fracture mechanisms, epidemiological aspects, symptoms, and specific related aspects of neuro-craniofacial injuries. The second part addresses the treatment of craniofacial trauma, examining operative principles and providing step-by-step descriptions of a variety of hard and soft tissue reconstructive procedures. Complications and late sequelae following craniofacial reconstruction are examined, and a further chapters is devoted to delayed reconstruction of craniofacial defects. New developments and the role of computer-assisted treatment planning are discussed in the final section. This manual will provide an indispensable reference for residents in maxillofacial training and for maxillofacial/ neurosurgeons in the specialized field of craniofacial traumatology. .
Classification and Diagnosis -- Anatomy of the Craniofacial Region -- Radiology of Craniofacial Fractures -- Classification of Craniofacial Fractures -- Mechanisms of Craniofacial Fractures -- Epidemiological Aspects of Craniofacial/Skull Base Fractures -- Craniofacial Fracture Symptoms -- Neurocranial Injuries in Craniofacial/Skullbase Fractures -- Therapy -- Surgical Repair of Craniofacial Fractures -- Methods of Dural and Skull Base Treatment -- Bone Grafts -- Osteosynthesis of Craniofacial Fractures -- Surgical Strategy for Complex Craniofacial Fractures -- Complications and Late Sequelae Following Craniofacial Reconstruction -- Delayed Reconstruction of Frontofacial Defects and Deformations -- A Treatment Algorithm in Craniofacial Reconstruction: Future Developments.
Keywords: Oral surgery; Maxillofacial surgery; Neurosurgery; Otolaryngologic surgery; Surgery; Oral and Maxillofacial Surgery; Neurosurgery; Head and Neck Surgery; General Surgery